Thermally Induced Carbohydroxylation of Styrenes with Aryldiazonium Salts - Kindt, Stephanie; Wicht, Karina; Heinrich, Markus (Angewandte Chemie International Edition, 2016)
The radical carbohydroxylation of styrenes with aryldiazonium salts has been achieved under mild thermal conditions. A broad range of aryldiazonium salts was tolerated, and the reaction principle based on a radical–polar crossover mechanism could be extended to carboetherification as well as to a two-step, metal-free variant of the Meerwein arylation leading to stilbenes.
Keywords: carbohydroxylation; diazonium ions; Meerwein arylation; radical reactions; styrene